Lifestyles and self-rated health, in Portuguese elderly from rural and urban areas. - Araújo, Joana (2011)
The perception of health status is essential for better planning in health, not only due to its role as a determinant of health, but also because it is related with the adoption of health-promoting behaviours. The aim of the present study was to explore the relationship between lifestyles and self-rated health, in Portuguese elderly, according to their residence in rural or urban areas. We evaluated 80 individuals from Rebordelo, Trás-os-Montes (rural area) and 383 from Porto (urban area), with 60 or more years and with four or less years of education. Data were collected by trained interviewers, through a structured questionnaire, to evaluate social, demographic, health and behavioural characteristics. Anthropometric measures were also obtained. Leisure-time physical activity, tobacco, alcohol and fruit and vegetable consumption were the lifestyles evaluated. To evaluate self-rated health, each person rated their health status, according to five options (excellent, very good, good, reasonable or poor), later grouped into two: poor versus the others. Odds ratio (OR) and 95% confidence intervals (95%CI) were calculated by unconditional logistic regression, after adjustment for sex and education. About 41% of the elderly from the rural area and 32% from the urban area rated their health status as poor. In multivariate analysis, in the rural area, poor self-rated health was inversely associated with the practice of leisure-time physical activity (OR = 0.22, 95%CI 0.06-0.80). In urban area, alcohol consumption was associated with a lower probability of self-rating health as poor (considering not drinking as reference, >0-15 g alcohol/day: OR = 0.42, 95%CI 0.24-0.72; >15 g alcohol/day: OR = 0.60, 95%CI 0.32-1.11). In the rural area, a positive association between fruit and vegetable consumption and poor self-rated health was found (≥ 5 vs.